Morphogenesis of Anthers Isolated From Cabbage (Brassica Oleracea L.) In Vitro - Kirakosyan, Rima; Kalashnikova, Elena (KnE Life Sciences, 2022)
This study aimed to optimize the steps of obtaining regenerated cabbage plants by direct embryogenesis from isolated anthers and ovaries. Stepwise pretreatment of inflorescences was usedfor the studied hybrids and inbred lines. First, the inflorescences were placed in water and kept at a temperature of +4-6∘C for one day without the use of biologically active substances. Then the inflorescences were placed in a solution of the drug Dropp (10 mg/l) and cultivated for two days. After that, the anthers and ovaries were isolated from the flower buds and cultured on the MS culture medium at a temperature of + 32∘C for one day. The cultivation of the isolated explants on a nutrient medium (containing 0.01 mg/lof Dropp, 1.0 mg/lof NAA, 500 mg/lof asparagine, 100 mg/l of tyrosine, and 10 g/l of sucrose)led to an increase in their morphogenetic potential in the culture of anthers and ovaries (by 3.42% and 5.54%, respectively).A cytological method was usedto demonstrate the haploid nature of the regenerating plants. The number of chromosomes in the root meristem andleaves, and the chloroplasts in the closing cells of the stomatawere calculated. Keywords: cabbage, culture in vitro, regenerated plants, anthers, ovaries, reproductive organs